American splendor - Berman, Shari Springer; Giamati, Paul; Bergman, Shari Springer; Pekar, Harvey; Pulcini, Robert; Good Machine Prodiction (Firm). ([Place of production not identified] Good Machine Production, 2003)
"Harvey Pekar is file clerk at the local VA hospital. His interactions with his co-workers offer some relief from the monotony, and their discussions encompass everything from music to the decline of American culture to new flavors of jellybeans and life itself. At home, Harvey fills his days with reading, writing and listening to jazz. His apartment is filled with thousands of books and LPs, and he regularly scours Cleveland's thrift stores and garage sales for more, savoring the rare joy of a 25-cent find. It is at one of these junk sales that Harvey meets Robert Crumb, a greeting card artist and music enthusiast. When, years later, Crumb finds international success for his underground comics, the idea that comic books can be a valid art form for adults inspires Harvey to write his own brand of comic book. An admirer of naturalist writers like Theodore Dreiser, Harvey makes his American Splendor a truthful, unsentimental record of his working-class life, a warts-and-all self portrait"--written by Sujit R. Varma
"Summary taken from https://www.imdb.com/title/tt0305206/?ref_=fn_al_tt_1
Produced by Rob Reiner ; music by Mark Shaiman; cinematography by John Seale.
Paul Giamati, Shari Springer Berman, Harvey Pekar.
VCD
In English.
Keywords: Drama; Comedy film